2013
DOI: 10.1614/ws-d-12-00068.1
|View full text |Cite
|
Sign up to set email alerts
|

A Trp574to Leu Amino Acid Substitution in the ALS Gene of Annual Bluegrass(Poa annua)Is Associated with Resistance to ALS-Inhibiting Herbicides

Abstract: Annual bluegrass is commonly controlled by acetolactate synthase (ALS)-inhibiting herbicides in managed turfgrass. An annual bluegrass population with suspected resistance to ALS-inhibiting herbicides was collected from Grand National Golf Course in Opelika, AL (GN population). Subsequent testing confirmed resistance of the GN population to foramsulfuron, trifloxysulfuron, bispyribac-sodium (bispyribac), and imazaquin when compared to a susceptible population collected locally at Auburn University (AU populati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
86
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(90 citation statements)
references
References 24 publications
4
86
0
Order By: Relevance
“…Trp 574 to Leu has been correlated in numerous species as target-site resistant amino acid substitution conferring resistance to multiple ALS-inhibiting herbicide families including sulfonylurea, imidazolinone and pyrimidinyl benzoic acids. 28,29 Considering that Glu 343 is not one of the 18 amino acid in the ALS-inhibiting herbicide-binding region, 30 and Trp 574 to Leu is historically correlated with target-site resistance, it can be concluded that an amino acid substitution to Leu 574 is the molecular mechanism of resistance. The sequencing results were aligned with mapping consensus sequences of both biotypes.…”
Section: Als Mutationmentioning
confidence: 99%
See 1 more Smart Citation
“…Trp 574 to Leu has been correlated in numerous species as target-site resistant amino acid substitution conferring resistance to multiple ALS-inhibiting herbicide families including sulfonylurea, imidazolinone and pyrimidinyl benzoic acids. 28,29 Considering that Glu 343 is not one of the 18 amino acid in the ALS-inhibiting herbicide-binding region, 30 and Trp 574 to Leu is historically correlated with target-site resistance, it can be concluded that an amino acid substitution to Leu 574 is the molecular mechanism of resistance. The sequencing results were aligned with mapping consensus sequences of both biotypes.…”
Section: Als Mutationmentioning
confidence: 99%
“…2). Double peaks in the ALS Trp 574 to Leu are indicative of heterozygosity or homeologous differences in the polyploid species, 29 either of which confer resistance to ALS-inhibiting herbicides. Based on this evidence, we can clearly state that there is an ALS isoform containing a Trp 574 -to-Leu substitution produced by the R biotype.…”
Section: Als Mutationmentioning
confidence: 99%
“…similar to susceptible (S) biotypes (Delyé et al 2004;Isgrigg et al 2002;Vaughn et al 1987). Therefore, pronamide may be an important tool for controlling annual bluegrass with resistance to DNA herbicides and other sites of action in turfgrass.There have been 28 cases of herbicide-resistant annual bluegrass reported worldwide (Heap 2016 glyphosate, sulfonylureas, and triazines used for POST annual bluegrass control in turfgrass (Binkholder et al 2011;Hutto et al 2004;Kelly et al 1999;McElroy et al 2013). A common mechanism of herbicide resistance in annual bluegrass and other weeds is a mutated target-site enzyme or protein (Anthony et al 1998;Cross et al 2015;McElroy et al 2013).…”
mentioning
confidence: 99%
“…There have been 28 cases of herbicide-resistant annual bluegrass reported worldwide (Heap 2016 glyphosate, sulfonylureas, and triazines used for POST annual bluegrass control in turfgrass (Binkholder et al 2011;Hutto et al 2004;Kelly et al 1999;McElroy et al 2013). A common mechanism of herbicide resistance in annual bluegrass and other weeds is a mutated target-site enzyme or protein (Anthony et al 1998;Cross et al 2015;McElroy et al 2013).…”
mentioning
confidence: 99%
See 1 more Smart Citation